2024
DOI: 10.1021/acscatal.4c00265
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Polyoxometalate-Stabilizing Pt Nanocatalysts for Quinoline Hydrogenation with Water-Mediated Dynamic Hydrogen

Xinjia Wei,
Yongjun Jiang,
Yuan Ma
et al.

Abstract: In this work, a Keggin-type platinum substituted polyoxometalate (POM) is constructed by the reaction of monolacunary phosphotungstate precursor [PW 11 O 39 ] 7− with chloroplatinic acid. The as-obtained tetrabutylammonium salt (TBA-PWPt) demonstrates that the dimeric Pt 2+ ions are incorporated into POM frameworks and linked by two monolacunary POM anions. Notably, once the Pt-substituted Keggin-type POM anion is reduced by H 2 , the POM anion-stabilizing Pt nanocatalysts are generated, which greatly facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Catalytic hydrogenation and hydrogenolysis are chemical processes used to modify or transform organic compounds by introducing hydrogen atoms into the molecular structure. POMs doped with Pd, 143 Pt 144–147 and Ru 148,149 nanoparticles (NPs) are reported to be efficient hydrogenation/hydrogenolysis catalysts. Han et al designed a multifunctional catalyst denoted as Pd NP/POM–IL composite supported on SiO 2 (Pd/H 2 [POM–IL]@SiO 2 ) for the reductive hydrolysis of C–O bonds in diaryl ethers in water, yielding selective ketone products in high yields (>80%) (Fig.…”
Section: The Catalytic Application Of Il–mocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic hydrogenation and hydrogenolysis are chemical processes used to modify or transform organic compounds by introducing hydrogen atoms into the molecular structure. POMs doped with Pd, 143 Pt 144–147 and Ru 148,149 nanoparticles (NPs) are reported to be efficient hydrogenation/hydrogenolysis catalysts. Han et al designed a multifunctional catalyst denoted as Pd NP/POM–IL composite supported on SiO 2 (Pd/H 2 [POM–IL]@SiO 2 ) for the reductive hydrolysis of C–O bonds in diaryl ethers in water, yielding selective ketone products in high yields (>80%) (Fig.…”
Section: The Catalytic Application Of Il–mocsmentioning
confidence: 99%
“…In quinoline hydrogenation, our recent investigation demonstrates that the POM anion-stabilizing Pt nanocatalysts can greatly facilitate to forming oxygen vacancies adjacent to Pt 0 species on POM catalysts. 147 The oxygen vacancy concentration of the POM catalyst exhibited a decisive role in the catalytic hydrogenation of quinoline in the aqueous media. Further studies indicated H 2 O actually participated in the hydrogenation and acted as an indirect hydrogen source.…”
Section: The Catalytic Application Of Il–mocsmentioning
confidence: 99%